PHYSIOLOGICAL AND MOLECULAR MARKERS FOR SALT TOLERANCE IN FOUR BARLEY CULTIVARS - Abdel-Hamid, A.M.E. (European Scientific Journal, ESJ, 2014)
The present investigation was carried out to detect physiological and molecular markers for salt tolerance in barley. Four cultivars of barley were screened for their tolerance against salt stress (9000 ppm). with respect to the performance of some physiological parameters such as germination percentage and abscisic acid (ABA) content and develop RAPD-PCR markers in barley linked to salt tolerance. The results of physiological analysis revealed a depression in germination percentages and an accumulation of abscisic acid (ABA) content in the stressed plants than those of the controls. The content of abscisic acid was much greater in the tolerant cultivars than in the sensitive ones. RAPD analysis was done utilizing six 10-mer random primers. The results showed the occurrence of some molecular genetic markers associated with salt tolerance. In conclusion, the physiological and molecular markers would be useful in screening different cultivars for their tolerance against salt stress during breeding programs of barley.